The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000480313
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Decreases Inflammatory Response in Human Lung Epithelial Cells by Inhibiting the Canonical NF-kB-Pathway

Abstract: Background/Aims: Alcohol (ethanol, EtOH) as significant contributor to traumatic injury is linked to suppressed inflammatory response, thereby influencing clinical outcomes. Alcohol-induced immune-suppression during acute inflammation (trauma) was linked to nuclear factor-kappaB (NF-ĸB). Here, we analyzed alcohol`s effects and mechanisms underlying its influence on NF-ĸB-signaling during acute inflammation in human lung epithelial cells. Methods: A549-cells were stimulated with interleukin (IL)-1β, or sera fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…In general, this setting is not comparable to our setting of an acute short-term exposure, which has been linked to the anti-inflammatory effects of ethanol [18]. Beside its capability of decreasing the pro-inflammatory cytokine levels in murine macrophages [38] or diminishing the adhesion of leukocytes to human lung epithelial cells [28], acute ethanol intake affects inflammasome activity. Upon acute ethanol administration, NLRP3 inflammasome activation was decreased by the inhibited oligomerization of ASC and lysosomal disruption [26].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In general, this setting is not comparable to our setting of an acute short-term exposure, which has been linked to the anti-inflammatory effects of ethanol [18]. Beside its capability of decreasing the pro-inflammatory cytokine levels in murine macrophages [38] or diminishing the adhesion of leukocytes to human lung epithelial cells [28], acute ethanol intake affects inflammasome activity. Upon acute ethanol administration, NLRP3 inflammasome activation was decreased by the inhibited oligomerization of ASC and lysosomal disruption [26].…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies revealed significant anti-inflammatory effects of acute ethanol administration upon the induction of inflammatory processes in different cell entities including human lung epithelial cells [28,30], but also in hepatic and neuronal inflammation [17,31]. Despite its immense clinical relevance, the influence of an acute intoxication with ethanol on inflammatory processes mediated by inflammasomes is mechanistically poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, IIR may lead to sepsis, systemic inflammatory response syndrome and multiple organ dysfunction syndrome [2]. IIR is also known to cause acute lung injury which in turn leads to a condition known as acute respiratory distress syndrome and contributes to the high mortality associated with IIR [3-5].…”
Section: Introductionmentioning
confidence: 99%
“…That we found a significant increase in alcohol-induced microglial apoptosis in our rodent model of acute alcohol use suggests the short-and long-term neurotoxic effects of alcohol use may be due in part to reductions in the reparative activity of microglia. Interestingly, alcohol could reduced Inflammatory Response in Human Lung Epithelial Cells [48].…”
Section: Discussionmentioning
confidence: 95%